Does Mental Health Affect the Decision to Vaccinate Against SARS-CoV-2? A Cross-Sectional Nationwide Study Before the Vaccine Campaign - Maciaszek, Julian; Lenart-Bugla, Marta; Szcześniak, Dorota; Gawłowski, Paweł; Borowicz, Wojciech; Misiak, Błażej; Rymaszewska, Joanna (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic generated a sense of threat in the society, leading to social isolation and mental health deterioration. A great deal of hope for the development of herd immunity was placed in preventive vaccinations. The survey, performed before vaccine campaign between September 26-October 27, 2020, during the second wave of the SARS-CoV-2 pandemic in Poland with the Computer Assisted Web Interviews method. The study was partly community based and partly open to the public. Participants were invited to complete the survey using Google forms via social media (Facebook, WhatsApp). The survey was also distributed 54 times at the request of interested persons via e-mail. Total 1043 questionnaires were assessed for eligibility and 41 were excluded (13 because of the age under 18, and 28 due to refusal to participate: non-response after sending questionnaire via e-mail). Finally 1001 questionnaires were included to the study and statistical analysis was performed on the basis of the 1001 responses. The questionnaire consisted of three parts: a sociodemographic survey, a questionnaire assessing the knowledge of the SARS-CoV-2 and the General Health Questionnaire-28. Participants also determined their attitude towards being vaccinated against SARS-CoV-2. The questionnaire was completed by a total of 1,001 participants: 243 people declared that they will not get vaccinated against SARS-CoV-2. Majority of people declaring the willingness to vaccinate were representatives of medical professions, suffering from chronic diseases, with higher values on the total GHQ-28 scale and the subscales: anxiety and insomnia, social dysfunction and somatic dysfunction. Loss of income, difficult access to health care, recognizing the restrictions as excessive and knowledge about COVID-19 were found as significant positive determinants of the reluctance to vaccinate. Greater readiness to vaccinate can be associated with greater certainty about its effectiveness and a hypothetical collectivist attitude. Experiencing anxiety and psychopathological symptoms are risk factors for infection, but can also be conducive to reliance on information about vaccination presented in the media. Reluctance to vaccinate may result from greater awareness of the complexity of the disease, and thus less faith in the effectiveness of vaccines.